2020
DOI: 10.1007/s10877-020-00513-y
|View full text |Cite
|
Sign up to set email alerts
|

Refeeding syndrome: multimodal monitoring and clinical manifestation of an internal severe neurotrauma

Abstract: Refeeding syndrome (RFS) is a rare, potentially life-threatening, condition seen in malnourished patients starting refeeding. RFS may provoke seizures and acute encephalopathy and can be considered an internal severe neurotrauma in need of specific treatment. The objective was to describe course of disease, treatment and, for the first time, multimodal monitoring output in a comatose patient suffering RFS. After gastric-banding and severe weight loss, the patient initiated self-starving and was transferred to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Sundström et al reported a case in which the patient suffered from a disturbance of consciousness during the refeeding period from prolonged malnourishment due to causes other than AN, and intracranial pressure monitoring (ICP) showed a marked increase in intracranial pressure. In their case report, the initial calorie level was 1800 kcal/day, which was higher than recommended and suggested to be a risk factor for cerebral edema [14].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Sundström et al reported a case in which the patient suffered from a disturbance of consciousness during the refeeding period from prolonged malnourishment due to causes other than AN, and intracranial pressure monitoring (ICP) showed a marked increase in intracranial pressure. In their case report, the initial calorie level was 1800 kcal/day, which was higher than recommended and suggested to be a risk factor for cerebral edema [14].…”
Section: Discussionmentioning
confidence: 86%
“…It is known that when refeeding severely undernourished patients, electrolytes are transferred into the cells due to an increase in insulin concentration caused by elevated blood glucose levels, resulting in a decrease in serum phosphorus, potassium, and magnesium levels, and this condition is known as refeeding syndrome [2,[9][10][11][12]. Many published guidelines recommend an initial calorie level of 10 kcal/day for high-risk patients and 5-10 kcal/day for very high-risk patients to prevent RS [2,[9][10][11][12]14]. Although the initial calories in the present case were within the recommended range, it is possible that the patient had a sudden change due to fatal arrhythmia.…”
Section: Discussionmentioning
confidence: 99%